Ocular Manifestations in Rheumatoid Arthritis - Boonsopon S. (2023)
Rheumatoid arthritis (RA) is an inflammatory rheumatic disease that generally damages synovial-line joints. Extra-articular manifestations of RA have been reported in cases of multiorgan involvement. These manifestations can occur in the hematologic and cardiovascular system, lungs, kidneys, and eyes. Various ocular manifestations of RA have been previously reported including keratoconjunctivitis sicca, conjunctivitis, uveitis, scleritis, retinal vascular occlusion, optic neuritis, and amaurosis fugax. It is important to recognize these ocular issues as manifestations of RA since they can sometimes be a response marker for the onset of an immune reactivation. Urgent management of ocular complications is essential to manage sight-threatening complications and prevent further damage to the eyes.